Data from: Origins and functional diversification of salinity-responsive Na+, K+ ATPase α1 paralogs in salmonids - Dalziel, Anne C.; Bittman, Jesse; Mandic, Milica; Ou, Michelle; Schulte, Patricia M. (2014)
Dryad version number: 1 Version status: submitted Dryad curation status: Published Sharing link: https://datadryad.org/stash/share/0Ls1klDRirqESEc_TFuRAE4lHN78OpUGiqgMb519mM4 Storage size: 237083 Visibility: public Usage notes Key for Figure 2 Accession numbers for all sequences used in Figure 2 and the short name used in sequence files for PAML and alignments (Appendix S1). Fig2_SequenceIDs_to_GenbankNumbers.txt Fig4- Pike real time data Gene expression of Na+, K+ ATPase paralogs and 18S in the Northern Pike (Esox lucius) Fig4_Pike real time datal.xls Supplementary Fig1 Teleost Na+, K+ ATPase α1 (ATP1A1) gene tree reconstructed using Bayesian inference (BI) with MrBayes version 3.2.1 (Ronquist et al. 2012) and the GTR+I+Γ model of nucleotide evolution. SuppFig1_MrBayes_Jan_7_2013.rtf Supplementary Figure 2 Teleost Na+, K+ ATPase α1 (ATP1A1) gene tree reconstructed using the maximum likelihood (ML) method with RAxML software version 7.2.7 (Stamatakis 2006) and the GTR+Γ model of nucleotide evolution. SuppFig2_RAxML_Dec_30.rtf Tree file for PAML Tree file to be used with the one and free ratios models in PAML (Table 1, Test 1a). ATP1A1.trees Control file for PAML - Branch Model Control file for PAML branch model to test for selection along Branch D of Fig.2 (Table 1). BranchModel_BranchD.ctl Tree file for PAML - 2 Tree file for PAML's Branch-Site Model A (testing for selection along Branch D of Fig.2. Table 3) BranchModel_BranchD.trees Control file for PAML - Branch Null Model Control file for the null PAML Branch Model testing for selection along Branch D in Figure 2 (Table 1). BranchModel_BranchDnull.ctl Control file for PAML - Branch-Sites Model Control file for PAML`to run Branch-sites Model A along branch D in Figure 2 (Table 3). BranchSite_BranchD.ctl Tree file for PAML - 3 Tree file for PAML's Branch-Site Model A, testing for selection in sites along Branch D in Figure 2 (Table 3). BranchSite_BranchD.trees Control file for PAML Branch-Site Null Model Control file for PAML's null Branch-site Model A testing ...